Hybrid Funding Innovation Based on Debt and Equity Collaboration for MSME Funding in North Sumatera - Nicholas Marpaung; Faisal Eriza; Revivo Praise Manurung; Ahmad Luthfi Fauzan; Gira Madoli Sitorus (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Micro, small, and medium enterprises (MSMEs) in North Sumatera facepersistent financing constraints that limit their contribution to regional economiccompetitiveness. Despite the proliferation of peer-to-peer (P2P) lending andsecurities crowdfunding platforms, pure debt and pure equity models exhibitstructural limitations: P2P lending suffers from high default risk and informationasymmetry, while equity crowdfunding imposes excessive dilution costs andvaluation challenges for early-stage MSMEs. This conceptual paper proposes ahybrid debt-equity funding model that integrates complementary financinginstruments through digital platforms, addressing these limitations by optimizingrisk allocation, reducing information frictions, and matching investor preferencesto firm lifecycle stages. Grounded in Capital Structure Theory, FinancialIntermediation Theory, Information Asymmetry frameworks, and AgencyTheory, the model demonstrates theoretical superiority over single-instrumentapproaches. North Sumatera serves as a critical testing ground due to itssubstantial MSME sector (contributing 57.8% to regional GDP), documentedcapital access barriers (only 15.2% of MSMEs receive bank loans), andsupportive regulatory environment under Indonesia's OJK fintech framework.Through conceptual development and policy analysis, this study presents atheoretically robust framework, comparative performance analysis, andimplementation roadmap. The hybrid model offers a scalable solution to bridgethe MSME financing gap in emerging markets, with implications for financialinclusion policy and platform governance